2018
DOI: 10.1111/jfd.12878
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variability of myxozoan parasite, Myxobolus inornatus, prevalence in young of the year smallmouth bass in the Susquehanna River Basin, Pennsylvania

Abstract: A myxozoan parasite, Myxobolus inornatus, is one disease agent identified in young of the year (YOY) smallmouth bass in the Susquehanna River Basin, Pennsylvania. We investigated spatial and temporal variability in M. Inornatus prevalence across the Susquehanna River Basin and at several out-of-basin sites. We examined potential land use drivers of M. Inornatus prevalence including agricultural and developed land use. In 1,267 YOY smallmouth bass collected from 32 sites during 2013-2016, M. Inornatus was docum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Myxozoans (phylum Myxozoa Grasse) have long been regarded as a class of protozoa, but more recent evidence suggests that they are highly differentiated metazoan parasites that infect invertebrates and aquatic animals as the main hosts 2628 . Metazoans predominantly infect fish 26 , with limited activity on platyhelminth, reptiles, and amphibians 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Myxozoans (phylum Myxozoa Grasse) have long been regarded as a class of protozoa, but more recent evidence suggests that they are highly differentiated metazoan parasites that infect invertebrates and aquatic animals as the main hosts 2628 . Metazoans predominantly infect fish 26 , with limited activity on platyhelminth, reptiles, and amphibians 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Several of the parasites that have been identifi ed have complex life cycles (e.g., myxozoans, trematodes, and cestodes; Figure 1 ) that can be infl uenced by host and environmental interactions. For example, the prevalence of a myxozoan parasite, M. inornatus , is likely to be infl uenced positively by agriculture land use, indicating that land use practices in the watershed could be contributing to infection rates (Schall et al 2018 ). One possible explanation is that nutrient and sediment inputs from agricultural activities may be altering instream habitat and subsequently increasing the availability of suitable habitat conditions for invertebrate host populations (e.g., aquatic oligochaetes; Kaeser and Sharpe 2006 ).…”
Section: Results and Discussion Temporal Changes In Catch Rates Mortmentioning
confidence: 99%
“…In studies analyzing land use and fish health metrics, spatial scale has been determined to be influential. Previous work has found associations between land use at the local scale and physiological processes in fish (Jeffrey et al 2015), parasite abundance (Schall et al 2018) and parasite diversity (Blanar et al 2016 (Schall et al 2018).…”
Section: Discussionmentioning
confidence: 97%
“…Many stream ecology studies focus on land use at the local scale; however, due to the high interconnectivity of riverine systems, large scale analyses should also be considered (Allan 2004). In a previous study on YOY SMB, agNHD positively predicted M. inornatus infections and infection rates were suggested to be influenced by increased nutrification and the myxozoan intermediate host (Schall et al 2018). The results of the current study showed agriculture and development at multiple spatial scales can be used to model coinfections and liver helminth prevalence in YOY SMB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation